STRATEGI MEMBANGUN BRAND ENGAGEMENT IKLAN SIRUP MARJAN PADA FESTIVE SEASON - Suryani, Ita; Marta, Rustono Farady; Chinmi, Maichel (Jurnal Komunikasi dan Kajian Media, 2023)
PT Lasallefood Indonesia is a beverage-producing company, namely Marjan. This Ramadan moment was taken advantage of by Marjan Syrup to issue a new advertisement, released and premiered on February 25, 2023, on television. Carrying the theme "Baruna the Guardian of the Ocean". The aim to be achieved is how Marjan Syrup advertising strategy can take advantage of the 2023 Ramadhan festive season in building brand engagement with consumers. a qualitative approach with a case study research method is used or a single case study with the object of research namely discussing Marjan syrup advertisements. From problems raised, this concludes the success of the advertisement is related to brand engagement can be seen from the following five points: (1) Consistency comes before Ramadhan, (2) Presenting different versions of stories, (3) Out of the box advertising concepts (4) Products which are suitable for special moments and (5) viral effects.